2017
DOI: 10.1123/iscj.2016-0120
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Collegiate Coaches’ Intentions to Advance Their Leadership Careers? The Roles of Leader Self-Efficacy and Outcome Expectancies

Abstract: The purpose of the current study was to examine the influences of leader self-efficacy and coaching career outcome expectancies on intentions for advancement in leadership careers of collegiate assistant coaches in the United States. We also investigated psychosocial antecedents of these factors and explored gender differences. Female and male collegiate assistant coaches (N = 674) participated in an online survey consisting of measurements of leadership career advancement intentions, leader self-efficacy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Some very important social phenomena such as the "glass ceiling" help to explain the barriers that hinder women's access in higher-ranking positions in the professional hierarchy. The predominance of men in management positions, hiring by similarity, the ideia of unequal competence, gender stereotypes and discrimination and difficulties in balancing personal life and work are some of the factors that cause these kinds of barriers to emerge (KILTY, 2006;LAVOI;DUTOVE, 2012;BURTON, 2015;MACHIDA-KOSUGA et al, 2017;CARSON, MCCORMACK;WALSH, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some very important social phenomena such as the "glass ceiling" help to explain the barriers that hinder women's access in higher-ranking positions in the professional hierarchy. The predominance of men in management positions, hiring by similarity, the ideia of unequal competence, gender stereotypes and discrimination and difficulties in balancing personal life and work are some of the factors that cause these kinds of barriers to emerge (KILTY, 2006;LAVOI;DUTOVE, 2012;BURTON, 2015;MACHIDA-KOSUGA et al, 2017;CARSON, MCCORMACK;WALSH, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, associating male characteristics with a sport coach position results in the prevalence of the ideal of unequal competence between men and women, which brings an inadequate conception of self-efficacy in women who occupy these positions (KILTY, 2006;MACHIDA-KOSUGA, et al, 2017), the need for constant self-assertion and, also, gender discrimination and homophobia, by not presenting the standard of heterosexual masculinity (LAVOI; DUTOVE, 2012; CARSON; MCCORMACK; WALSH, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Caligiuri and Dragoni (2015) stated, "The concern regarding the short supply of global leaders is exacerbated by the speed in which future leaders will need to be developed" (p. 226). While specific contextual research has been conducted regarding the role of leadership self-efficacy in Latina leaders in higher education (Montas-Hunter, 2012), educators and students (Bang & Reio, 2017;Phan & Locke, 2015), career advancement of women coaches (Machida & Feltz, 2013), business leaders (Javadin et al, 2016;Paglis & Green, 2002;Walumbwa et al, 2005), and women leaders in the credit union industry (Garmon, 2007), no research was found within the field of international agricultural development. Thus, research is needed to explore the lived leadership development experiences of NGO executive leaders in international agricultural development.…”
Section: Introductionmentioning
confidence: 99%
“…In sport specifically, we are seeing the number of women in leadership decreasing (Demers, Thibault, Brière, & Culver, 2019). There has been a notable shortage in female head coaches in the United States (Machida-Kosuaga, Schaubroek, Gould, Ewing, & Feltz, 2017) and a general underrepresentation of women in sport leadership positions on a global scale (LaVoi, 2016). Moreover, the number of women securing board membership positions on Canadian National Sport Organizations (NSOs) is consistently less than 30% (CAAWS, 2018).…”
mentioning
confidence: 99%
“…When women did secure coaching positions, they experienced a host of additional barriers as they attempted to take on new leadership roles. These barriers included perceived gender discrimination, which impacted the coaches' intentions to advance into leadership positions, and fewer opportunities to participate in developmental challenges than their male counterparts (Machida-Kosuaga et al, 2017). In addition, Burton (2015) found males were predominantly holding the gatekeeper roles for delegating new leadership positions and tended to be favorable towards hiring men.…”
mentioning
confidence: 99%